Thermal deoxygenation causes photoluminescence shift from UV to blue region in lyophilized graphene oxide1. Issue 91 (9th October 2015) - Kumar, Veeresh; Kumar, Vivek; Reddy, G. B.; Pasricha, Renu
<x xml:space="preserve">Abstract</x> Lyophilized graphene oxide (GO) was thermally exfoliated in stages at predefined temperatures up to 400 °C and the photoluminescence (PL) study of GO and thermally reduced GO (TGO) was carried out at each step.